STUDENTS’ ABILITY IN USING CONJUNCTION IN WRITING NARRATIVE TEXT AT THE ELEVENTH GRADE OF SMK NEGERI 1 TELUK DALAM - Zebua, Agustini; Laia, Mohamad Yunus (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2024)
This research aimed at analyzing students’ ability in using conjunction in writing narrative text at the eleventh grade of SMK Negeri 1 Teluk Dalam. The kind of this research is qualitative research with descriptive approach. Researcher used Miles, Huberman, & Saldana theory to analyze the students’ ability in using conjunction in writing narrative text. The result of this research showed the students had the ability in using conjuction within a naraive text. It showed by the students’ worksheet that each conjuctions were used by students was exactly. It means that, they could be able to connects the elements are contained within a text well. The conjuction that students more used were coordinating conjuction and subordinating conjuction. However, they still have difficulties in using conjuction within a narrative text especially in using correlation conjunction. Those students’ difficulties caused by the students’ comprehension of narrative text materials, especially in using conjuction. So the students could not comprehend it and regarded that it is difficult. It is suggested that students should pay attention about the students’ ability in using conjunction in order to create a good text as well as a speech. For the teachers, hopefully this research could be used as their consideration to teach conjuction to students. For the next researcher, could be the information and knowledge to create a narrative text.